Efek Pencampuran Bahan Pestisida Nabati Terhadap Keefektifannya Dalam Menekan Colletotrichum sp. In Vitro Serta Penyakit Antraknosa Pada Stroberi - Noor Istifadah; Anggi Ayuningtyas; Ceppy Nasahi (Faculty of Agriculture, Pattimura University, 2017)
Antrachnose disease caused by Colletotrichum sp. is one of the important diseases of strawberry in the field or after postharvest. The environmentally-friendly control measures is the use of botanical pesticides. Botanical pesticides that are commonly used by the farmers are mixture of several kinds of plant extract. This paper discuses the effects of combining water extract of garlic, galangal rhizome, and betel leaves on their efficacy in inhibiting conidial germination of Colletotrichum sp., the growth of miselium in vitro and the development of antracnose disease in strawberry. Preliminary study was conducted to determine the concentration of the extract that was used for further experiment. The experiment was arranged in the completely randomized design with 10 treatments involving water extract of garlic, galangal rhizome, betel leaves and their mixtures, fungicide and control/check. Each treatment was repeated three times.The results showed that combination of water extract of garlic, galangal rhizome and betel leaves did not enhance their efficacy. The inhibition effect of garlic water extract (5% concentration) was relatively better than its mixtures with galangal and betel leaves (total concentration 15%). The effects of galangal rhizome or betel leaves water extract and their mixtures were not significantly different. Water extract of garlic (15 %) inhibited Colletotrichum sp. which was showed by inhibition zone of 9.3 mm width; and suppressed the antrachnose disease in strawberry stolon by 83,7 %.